2021
DOI: 10.1002/ase.2064
|View full text |Cite
|
Sign up to set email alerts
|

Zimbabwean PreClinical Medical Students Use of Deep and Strategic Study Approaches to Learn Anatomy at Two New Medical Schools

Abstract: Anatomy is a challenging preclinical subject owing to the vast amount of information that students need to master. The adoption of relevant study approaches is key to the development of a long-lasting understanding of anatomical subject matter. Phenomenographic educational research describes the medical students as using a variable mix of deep, strategic, and surface approaches to study. Continually assessing students' learning preferences and approaches is crucial for achieving the desired learning outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Using this line of thought would make it appear as though the current learners are not self‐regulating or lack the motivation to use specific study strategies since most of the constructs did not correlate significantly with learning outcomes (anatomy cGPA). However, a recent Zimbabwean study showed that medical students directed their own learning and predominantly used strategic and deep learning strategies that support academic performance (Zilundu et al, 2021). Follow‐up interviews with the current sample revealed that students suffer from stress as well as test anxiety and are not directly supported by the institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this line of thought would make it appear as though the current learners are not self‐regulating or lack the motivation to use specific study strategies since most of the constructs did not correlate significantly with learning outcomes (anatomy cGPA). However, a recent Zimbabwean study showed that medical students directed their own learning and predominantly used strategic and deep learning strategies that support academic performance (Zilundu et al, 2021). Follow‐up interviews with the current sample revealed that students suffer from stress as well as test anxiety and are not directly supported by the institution.…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up interviews with the current sample revealed that students suffer from stress as well as test anxiety and are not directly supported by the institution. They also revealed that despite their strategic approach to anatomy study (Zilundu et al, 2021), the examinations are still difficult and there are high chances that what one knows does not appear in continuous assessment examinations. These factors suggest that anatomy teachers need to reflect on their assessments as well as providing institutional psychosocial support to students who are often under pressure to do better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who rely on a deep approach to learning try to understand the meaning and make connections between ideas and information, think critically, capture the logical structure underlying the content or information as well as the related source, they are able to explain the content to another student and build their own understanding of course materials and they transform the knowledge (Alt & Boniel-Nissim, 2018;Azewara et al, 2021;Hu & Yeo, 2020;Lindblom-Ylä nne et al, 2019;Omar, 2021). In contrast, students who use a surface approach memorize facts without understanding them, use a minimum of effort and engagement, they passively receive ideas and concepts without questioning them and learn them by heart in order to pass a course, to meet the assessment demand, they are led by the fear of failure, motivated by a deadline (Alhammadi, 2021;Alt & Boniel-Nissim, 2018;Chue, 2022;Zilundu et al, 2022). The surface approach has been found to imply unreflective learning (Lindblom-Ylä nne et al, 2019).…”
Section: Approaches To Learning: Conceptmentioning
confidence: 99%
“…Anatomy education has been described as critical for good clinical practice among medical, dental and allied health professionals [ 12 ]. However, the study of anatomy requires the understanding and retention of large volumes of information [ 13 ]. In recent years, there has been a reduction in the amount of time dedicated to teaching anatomy in many healthcare programmes [ 14 16 ], resulting in a focus on students to engage in self-directed learning [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%